Mycobacterium bolletii Respiratory Infections - Toïdi Adékambi; Michel Drancourt (Emerging Infectious Diseases, 2009)
Contrary to other species in the Mycobacterium chelonae-abscessus complex, we reidentified M. bolletii strains isolated from 4 respiratory patients and found these strains to be uniformly resistant to clarithromycin. No mutations previously associated with macrolide resistance in bacteria were detected in either the 23S rDNA or the genes encoding riboproteins L4 and L22.